Unpacking components of sustainable and resilient urban food systems. (1st November 2018) - Vieira, Leticia Canal; Serrao-Neumann, Silvia; Howes, Michael; Mackey, Brendan
Abstract: Urban food systems are connected with several pressing issues, including urban population growth, resource scarcity, and climate change. To cope within these issues, urban food systems need to become more sustainable in their practices, as well as resilient in the face of extreme weather events. While scholars have started to investigate this topic, no comprehensive analysis has yet addressed what entails sustainable and resilient urban food systems. Through a systematic review of the literature, this paper aims to improve our understanding of the key components of sustainable and resilient urban food systems. This study reviewed 53 publications and identified components related to the health, social, economy, environment, and governance domains. Only 5 of the works included in the review discussed sustainability and resilience to the impacts of climate change in urban food systems simultaneously, so there is an opportunity for original research and analysis. The most frequently identified components of urban food systems relate to: access to healthy food; connectivity between urban and rural areas; having a strong local food economy and food production; reducing food waste; and, having active participation of all actors in decision making. There is some level of consensus on linking sustainability and resilience, but diversity in food sources and the development of social capabilities need to be emphasised for climate change adaptation. Highlights: The idea of a localised food system is strongly present in the reviewed publications. Few studies discuss both sustainability and resilience in urban food systems. It is feasible to integrate the sustainability and the resilience approach. For climate change adaptation it is necessary diversity and knowledge generation. It is necessary to investigate how the outcomes can be fostered in urban food systems.